2020
DOI: 10.1089/mab.2020.0022
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and Safety of Anti-Interleukin-17A Monoclonal Antibody Secukinumab in Treatment of Ankylosing Spondylitis: A Meta-Analysis

Abstract: Different signaling pathways have been studied in ankylosing spondylitis. New treatment options such as secukinumab could have an important role inhibiting the release of proinflammatory cytokine IL-17. The aim of this study was to compare the efficacy and safety of secukinumab in ankylosing spondylitis. A systematic review was conducted using MEDLINE and EMBASE databases to identify randomized clinical trials (RCTs) that assess the role of secukinumab in ankylosing spondylitis. The variables were safety (tota… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 17 publications
0
3
0
Order By: Relevance
“…The magnitude and direction of the primary endpoint results from the MEASURE studies have been confirmed in meta-analyses [ 26 , 27 ]. Similarly, these studies showed significant improvements in the secondary endpoints of disease activity, such as C-reactive protein (CRP) levels, Ankylosing Spondylitis Disease Activity Score (ASDAS), and Bath Ankylosing Spondylitis Disease Activity Index (BASDAI), relative to placebo [ 16 , 19 21 ].…”
Section: Methodsmentioning
confidence: 89%
“…The magnitude and direction of the primary endpoint results from the MEASURE studies have been confirmed in meta-analyses [ 26 , 27 ]. Similarly, these studies showed significant improvements in the secondary endpoints of disease activity, such as C-reactive protein (CRP) levels, Ankylosing Spondylitis Disease Activity Score (ASDAS), and Bath Ankylosing Spondylitis Disease Activity Index (BASDAI), relative to placebo [ 16 , 19 21 ].…”
Section: Methodsmentioning
confidence: 89%
“…The pillars of treatment for ankylosing spondylitis are nonsteroidal anti-inflammatory drugs, which provide greater relief from spinal pain and moderate benefit in restoring body function. However, NSAIDs can only strictly control symptoms; they are a class of anti-inflammatory drugs that do not contain steroidal structures; the drugs have anti-inflammatory, antiicoagulant, anti-rheumatic, analgesic and antipyretic effects; they do not alter the course of the disease or prevent structural damage.Corticosteroids, Anti-TNF [5], interleukin 17A [6] [7] and various dark and emerging biologic therapies are also frequently used in clinical settings to treat AS patients. However, the results of these treatments have not been satisfactory.…”
Section: Western Medical Pathogenesis and Treatmentmentioning
confidence: 99%
“…Secukinumab (monoclonal antibody to IL-17A) is effective in psoriasis. 16 A new drug for PsA treatment (Apremilast) is an inhibitor of phosphodiesterase-4 16 ; its favorable safety profile in the absence of the need for regular blood monitoring and hepatotoxicity may be an advantage in practice. Prior to administering genetically engineered biological preparations (GEBP), it is necessary to perform the examination for tuberculosis, X-ray of the thoracic cavity, every 6 months it is necessary to assess the dynamics of these indicators.…”
Section: Treatment Historymentioning
confidence: 99%